Closure of Large Pressure Ulcers utilizing the Principles of Limberg flap - P Kumar; K G Bhaskara (Indian Journal of Plastic Surgery)
A prospective study of 17 patients (21 Limberg flaps in 19 pressure ulcers) was done to establish the efficacy of Limberg flap.. Limberg flaps were used in only those cases where primary closure was not possible. This flap was found to be simple to execute and short-term results were satisfactory. Also, it spares underlying muscles for future use. None of the flaps showed necrosis. Partial wound dehiscence was noticed in 7 (33.33%) cases, which was managed by secondary suturing in four cases, by split skin graft in one case and by second Limberg flap in one case.